Baking process design based on modelling and simulation: Towards optimization of bread baking - Purlis, Emmanuel (2012)
This paper presents a theoretical approach for optimal design of the baking process. Conventional baking of bread was taken as subject of study, and simulation of previously validated models was used to investigate the process. The proposed approach is based on the definition of two different times for the baking process: a critical time, i.e. a minimum baking time assessed by the complete starch gelatinization in the product, and a quality time, i.e. the time necessary to achieve a target value for a given quality attribute. In this work, browning determined the quality time due to its relevance with regard to sensory and nutritional aspects. As a result, feasible solutions are obtained involving a minimum baking (acceptable products) and a minimum thermal input for a given value of browning, which helps to reduce the formation of acrylamide. Optimum solutions can be then obtained by defining specific objectives; weight loss can be minimized by lowering the value of heat transfer coefficient. Furthermore, obtained results can be helpful to build more efficient ovens.